2010
DOI: 10.1007/s11219-010-9103-x
|View full text |Cite
|
Sign up to set email alerts
|

Automatically identifying changes that impact code-to-design traceability during evolution

Abstract: An approach is presented that automatically determines if a given source code change impacts the design (i.e., UML class diagram) of the system. This allows code-todesign traceability to be consistently maintained as the source code evolves. The approach uses lightweight analysis and syntactic differencing of the source code changes to determine if the change alters the class diagram in the context of abstract design. The intent is to support both the simultaneous updating of design documents with code changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…Stefan W. et al investigated the traceability in requirements engineering and model-driven development [125]. To determine if a given source code change impacts the design of the system, Maen H. et al presented an automatic approach that allows code-to-design traceability to be consistently maintained the evolvement of source code [126]. A framework called iTrace was proposed for the management and analysis of traceability information of different models in MDE projects [127].…”
Section: Observability and Traceabilitymentioning
confidence: 99%
“…Stefan W. et al investigated the traceability in requirements engineering and model-driven development [125]. To determine if a given source code change impacts the design of the system, Maen H. et al presented an automatic approach that allows code-to-design traceability to be consistently maintained the evolvement of source code [126]. A framework called iTrace was proposed for the management and analysis of traceability information of different models in MDE projects [127].…”
Section: Observability and Traceabilitymentioning
confidence: 99%
“…However, empirical results have shown that obtaining fine-grained traceability links does not necessarily outweigh the cost of extracting them [2]. Finally, it has been found that vertical traceability links do not tend to propagate their changes bottom-up (i.e., changes in code are unlikely to affect the design) [3].…”
Section: Related Workmentioning
confidence: 99%
“…Our TraceLab based solution tries to accommodate both needs (separately of course). One way to accommodate the user needs is by offering multiple ways to recovering the traceability links [10].…”
Section: The Traceability Recovery Processmentioning
confidence: 99%